Environmental Isotope Study (14C, 13C, 18O, D, Noble Gases) on Deep Groundwater Circulation Systems in Hungary With Reference to Paleoclimate. Issue 3 (18th July 2016) - Stute, Martin; Deak, Jozsef
Abstract : We have studied environmental isotopes and noble gases in groundwater samples from various locations in the Great Hungarian Plain along two selected hydrogeological cross-sections of ca 100km. The 14 C groundwater ages were corrected hydrochemically and compared with age information derived from excess helium due to 4 He from α-decay of U and Th and their daughter nuclides within the aquifer and to He accumulation from the crustal (and mantle) He flux. In correcting the 14 C groundwater ages, we considered carbonate dissolution under open and closed system conditions in the infiltration areas. Non-radioactive reduction of the 14 C/ 12 C isotope ratio also plays an important role due to the addition of "dead" carbon species to groundwater along its subsurface pathway. High (corrected) 14 C ages, which fall into the last global cold period, are supported by significantly lower heavy stable isotope values as well as lower temperatures derived from the noble gases Ne, Ar, Kr and Xe.